B. h(x) + 41 = 31x2 + 77x
C. y = 31x2 + 77x − 41
D. y + 41 = 31x2 + 77x
Answer:
I think the answer is A. y= 31x2 + 77x + 41
Step-by-step explanation:
The function h(x) = 31x2 + 77x + 41 can also be written as y = 31x2 + 77x + 41, as y is often used interchangeably with f(x) or h(x) in mathematical functions. The remaining options do not accurately reformulate the original equation.
The function
h(x) = 31x2 + 77x + 41
can also be written as
y = 31x2 + 77x + 41
. This is because in mathematical functions, y is often used interchangeably with f(x) or h(x), representing the output or dependent variable. It's important to note that, the other options do not correctly represent the original equation. In Option B, the constant term is incorrectly added to the function on the left side; in Option C, the constant term is incorrectly subtracted; and in Option D, the constant term is incorrectly added to 'y' on the left side.
#SPJ11
3x3 + 9x2 - 12x
If you factor 3x from the expression, you have
So, we have
We easily have
So, one solution is x=0.
The other solutions depend on the quadratic equation:
So, the solutions are